Theoretical Aspects of Enterprise Image Management (Economics and region, 2020)
The essence of the “enterprise image” concept is defined. The process of forming enterprise image is investigated and the main problems that arise during the implementation of this process are identified in the article. The main elements of the enterprise image structure are considered. It was found that a positive image of the enterprise contributes formation of an appropriate level of stakeholders trust to the company and helps to see specific benefits that competitors do not have, so the formation of the enterprise image is very important.
Keywords: image; classification; competitiveness; enterprise; functions of positive enterprise image